Synthesis of MoS2/graphene nanocomposite by facile ultrasonic-assisted hydrothermalmethod - Le Ngoc, Long; Pham Trung, Kien; Tran Van, Khai (Vietnam Journal of Science and Technology, 2019)
In this report, thin layers of MoS2 were in-situ incorporated into graphene oxide (GO) to form MoS2/graphene nanocomposite by a facile ultrasonic-assisted hydrothermal method. X-ray Diffraction (XRD) and Raman analysis revealed that the as-synthesized MoS2 nanosheets crystalized in hexagonal phase 2H-MoS2 while High Resolution Transmission Electron Microscopy (HRTEM) images confirmed that MoS2 layers with average thickness of 5–6 nm (6–8 layers) attached on the edges and surfaces of graphene sheets with high density and uniform shape restacking in three-dimensional (3D) architectures. The Scanning Transmission Electron Microscopy – Energy Dispersive X-ray spectrum (STEM-EDX) investigation further confirmed the low impurity of MoS2/graphene composite, and the well repairing of defects in GO surfaces during the hydrothermal process. Our approach is promising for a scalable, inexpensive, and accurate strategy to fabricate state-of-the-art materials with a certain structure for various practical applications such as electrode material for Lithium battery or supercapacitor.